Rootstocks on yield and on nutrient uptake and extraction in ‘BRS Vitória’ grapevine - Callili, Daniel [UNESP]; Tecchio, Marco Antonio [UNESP]; Sánchez, Camilo André Pereira Contreras [UNESP]; Campos, Olivia Pak [UNESP]; Teixeira, Luiz Antonio Junqueira; Campos, Leonardo Silva [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Leonel, Sarita [UNESP] (FapUNIFESP (SciELO), 2025)
‘BRS Vitória’ is the leading seedless table grape cultivar in tropical regions of Brazil, but there is a lack of information regarding suitable rootstocks for subtropical cultivation. This study aimed to evaluate the productive performance and nutrient cycling of ‘BRS Vitória’ grapevines grafted onto rootstocks ‘IAC 572’, ‘IAC 766’, and ‘1103P’ under subtropical climate conditions. Crop yield, nutrient content, and weight of shoots and bunches were assessed over two growing seasons, along with nutrient removal via pruning and harvest and nutrient utilization efficiency. The ‘IAC 572’ rootstock promoted greater shoot biomass accumulation and crop yield compared to ‘IAC 766’ and ‘1103P’. Both nutrient content and nutrient accumulation were also higher in grapevines grafted onto the ‘IAC 572’ rootstock. Nevertheless, the amount of nutrients transported to the bunch was comparatively lower than in ‘IAC 766’ and ‘1103P’. Given its superior productivity, nutrient accumulation capacity, and nutrient utilization efficiency, the ‘IAC 572’ rootstock is more suitable for ‘BRS Vitória’ grapevines in subtropical regions.
Keywords: grafting; hybrid grapes; seedless grapes; subtropical viticulture; table grapes